2021
DOI: 10.3390/ani11061692
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Phenotypes of Escherichia coli Isolates in Wild Canarian Egyptian Vultures (Neophron percnopterus majorensis)

Abstract: The presence of multidrug-resistant (MDR) Escherichia coli in cloacal samples from Canarian Egyptian vultures was investigated. Samples were obtained from chicks (n = 65) and from adults and immature birds (n = 38). Antimicrobial susceptibility to 16 antibiotics included in 12 different categories was determined for 103 E. coli isolates. MDR was defined as acquired non-susceptibility to at least one agent in three or more antimicrobial categories. Forty-seven different resistance phenotypes were detected: 31 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…All of the E. coli isolates and the K. pneumoniae isolates from the selective screening for extended‐spectrum cephalosporin resistance ( n = 52 for E. coli , n = 4 for K. pneumoniae , where three samples contained both E. coli and K. pneumoniae ) were defined as multidrug‐resistant (MDR) having resistance against ≥1 agent in ≥3 different antimicrobial categories (Supporting Information: Table S1 at https://doi.org/10.5281/zenodo.7645125 ) (Magiorakos et al, 2012 ). Thus at least 53% of the vultures carried MDR bacteria, which is higher than in a recent study with a comparable methodology that found 40% MDR E. coli in cloacal samples derived from Egyptian vultures in the Canary Islands (Suarez‐Perez et al, 2021 ). Furthermore, the prevalence of ESBL in this study (>50%) is higher than reported from vultures in the Canary Islands, where 22.7% ( n = 5/22) had ESBL phenotype (Carvalho et al, 2020 ).…”
Section: Resultsmentioning
confidence: 53%
“…All of the E. coli isolates and the K. pneumoniae isolates from the selective screening for extended‐spectrum cephalosporin resistance ( n = 52 for E. coli , n = 4 for K. pneumoniae , where three samples contained both E. coli and K. pneumoniae ) were defined as multidrug‐resistant (MDR) having resistance against ≥1 agent in ≥3 different antimicrobial categories (Supporting Information: Table S1 at https://doi.org/10.5281/zenodo.7645125 ) (Magiorakos et al, 2012 ). Thus at least 53% of the vultures carried MDR bacteria, which is higher than in a recent study with a comparable methodology that found 40% MDR E. coli in cloacal samples derived from Egyptian vultures in the Canary Islands (Suarez‐Perez et al, 2021 ). Furthermore, the prevalence of ESBL in this study (>50%) is higher than reported from vultures in the Canary Islands, where 22.7% ( n = 5/22) had ESBL phenotype (Carvalho et al, 2020 ).…”
Section: Resultsmentioning
confidence: 53%
“…All of the E. coli isolates and the K. pneumoniae isolates from the selective screening for extended-spectrum cephalosporin resistance (n=52 for E. coli, n=4 for K. pneumoniae, where three samples contained both E. coli and K. pneumoniae) were defined as multidrug-resistant (MDR) having resistance against 1 agent in 3 different antimicrobial categories (Table S1 at https://doi.org/10.5281/zenodo.7645125) (Magiorakos et al, 2012). Thus at least 53% of the vultures carried MDR bacteria, which is higher than in a recent study with a comparable methodology that found 40% MDR E. coli in cloacal samples derived from Egyptian vultures in the Canary Islands (Suarez-Perez et al, 2021). Furthermore, the prevalence of ESBL in this study (>50%) is higher than reported from vultures in the Canary Islands, where 22.7% (n=5/22) had ESBL phenotype (Carvalho et al, 2020).…”
Section: Phenotypic and Genotypic Resistance Characterizationmentioning
confidence: 81%
“…MDR was defined as non‐susceptibility to at least one agent in three or more antimicrobials categories of the following classes of antibiotics: third‐generation cephalosporins, fluoroquinolones, aminoglycosides, beta‐lactamase inhibitor combination and polymyxins (Magiorakos et al, 2012). XDR was defined as non‐susceptibility to at least one agent in all but two or fewer above‐mentioned antimicrobial categories (Suarez‐Perez et al, 2021). The host strain and the library strains were identified as E .…”
Section: Methodsmentioning
confidence: 99%